1965
DOI: 10.1016/s0006-3495(65)86759-5
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Criteria for Polypeptide and Protein Chain Conformations

Abstract: The conformation of a polypeptide or protein chain may be specified by stating the orientations of the two linked peptide residues at each alpha carbon atom in the chain, namely the two dihedral angles varphi, varphi' about the single bonds N-alphaC and alphaC-C' from a defined standard conformation. By using certain criteria of minimum contact distances between the various atoms, the allowed anges of (varphi, varphi') have been worked out for three values of the angle N-alphaC-C' (tau), namely 105, 110, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
317
1
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 740 publications
(331 citation statements)
references
References 15 publications
12
317
1
1
Order By: Relevance
“…First, this loop is folded in a compact fashion on the surface of the molecule (Figure 1). All residues have conformations within the favorable regions of the Ramachandran plot (35), in contrast to Ser150 in previous models, which was placed in an unfavorable region. Finally, the average temperature factor for the main-chain atoms within this loop is 36.0 Å 2 (or 38.8 Å 2 for all atoms of residues 144-152), compared with 60 Å 2 , the lowest previously reported (14) (for the structure with PDB code 1asw, also solved with a frozen crystal).…”
Section: Discussioncontrasting
confidence: 59%
“…First, this loop is folded in a compact fashion on the surface of the molecule (Figure 1). All residues have conformations within the favorable regions of the Ramachandran plot (35), in contrast to Ser150 in previous models, which was placed in an unfavorable region. Finally, the average temperature factor for the main-chain atoms within this loop is 36.0 Å 2 (or 38.8 Å 2 for all atoms of residues 144-152), compared with 60 Å 2 , the lowest previously reported (14) (for the structure with PDB code 1asw, also solved with a frozen crystal).…”
Section: Discussioncontrasting
confidence: 59%
“…A plot of R factor versus resolution (Luzzati, 1952) is shown in Fig. 2, a Ramachandran plot (Ramakrishnan & Ramachandran, 1965) in Fig. 3 and the distribution of average main-chain and sidechain temperature factors, for the principal conformers, is shown in Fig.…”
Section: Least-squares Refinementmentioning
confidence: 99%
“…Presumably they are highly disordered. The Ramachandran plot (Ramakrishnan & Ramachandran, 1965), produced by PROCHECK (Laskowski et al, 1993), is shown in Fig. 6.…”
Section: Accuracy Of the Modelmentioning
confidence: 99%